Providing Education about Hypertension in the Elderly at the Tresna Werdha Elderly Age Private House Posts 7 Sentani, Jayapura District - Nasrianti, Nasrianti; Hasnia, Hasnia; Patungo, Viertianingsih (Universitas Malahayati Lampung, 2024)
ABSTRACT Background The elderly group can trigger the emergence of various diseases such as arthritis, heart and blood vessels, hypertension. Body mass index (BMI) is directly correlated with blood pressure, especially systolic blood pressure. Elderly people who have a history of hypertension take hypertension medication, receive less education regarding hypertension, but are given regular check-ups, namely posyandu, by the nearest health center. Based on this, it is necessary to provide regular education or counseling about hypertension in the elderly. The method of implementing activities is carried out through an approach, namely analyzing the conditions of the target area, followed by identifying problems, planning interventions and carrying out implementation to overcome the planned problems by carrying out activities in the form of providing education, namely health promotion. associated with hypertension. As a result of observations from this health education activity, there were 3 elderly people who actively asked the instructor. Then the instructor answered questions from the elderly. After getting answers to their questions, the elderly people who asked seemed to understand. By administering traditional medicine to the elderly, several elderly people with hypertension experienced a reduction in blood pressure of 130/80 mmHg. Keywords: Education, Hypertension, Elderly